2013
DOI: 10.1016/j.bbmt.2013.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Nonrelapse Mortality and Mycophenolic Acid Exposure in Nonmyeloablative Hematopoietic Cell Transplantation

Abstract: We evaluated the pharmacodynamic relationships between mycophenolic acid (MPA), the active metabolite of mycophenolate mofetil (MMF), and outcomes in 308 patients after nonmyeloablative hematopoietic cell transplant. Patients were conditioned with total body irradiation ± fludarabine, received grafts from HLA-matched related (N=132) or unrelated (N=176) donors, and received post-grafting immunosuppression with MMF and a calcineurin inhibitor. Total and unbound MPA pharmacokinetics were determined to day 25; ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 36 publications
2
40
0
Order By: Relevance
“…Whether this difference is also seen in matched sibling and unrelated donor HCT remains to be seen, but suggests that higher MMF dosing may be beneficial. Previous studies have also demonstrated that there is inter-individual variation of plasma levels of mycophenolic acid (MPA), the active form of MMF, and that patients with lower concentration of MPA may have increased GVHD compared to higher levels [29][30][31][32]. While lower dosing may have contributed to the increased risk of severe GVHD, this further highlights the importance and lack of standard regarding the optimal dosing and length of MMF for GVHD prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this difference is also seen in matched sibling and unrelated donor HCT remains to be seen, but suggests that higher MMF dosing may be beneficial. Previous studies have also demonstrated that there is inter-individual variation of plasma levels of mycophenolic acid (MPA), the active form of MMF, and that patients with lower concentration of MPA may have increased GVHD compared to higher levels [29][30][31][32]. While lower dosing may have contributed to the increased risk of severe GVHD, this further highlights the importance and lack of standard regarding the optimal dosing and length of MMF for GVHD prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…7 We and others use mycophenolate mofetil (MMF) as part of the immune suppression regimen in HCT. 2, 3, 712 Our group previously demonstrated that a low unbound mycophenolic acid (MPA) area under the curve (AUC), which is the active metabolite of MMF, is associated with higher rates of graft failure and grade II–IV acute GVHD in RIC UCB, matched sibling, and adult unrelated donor transplantation. 13 In addition, a report of adult unrelated donor HCT using a fludarabine/total body irradiation (TBI)-based non-myeloablative conditioning regimen suggests superior engraftment with a higher MPA AUC.…”
Section: Introductionmentioning
confidence: 99%
“…(29) There is considerable interindividual variability in MPA plasma exposure with weight-based dosing of either intravenous or oral MMF in HCT recipients. (10, 30) Pharmacodynamic data suggest a relationship between clinical outcomes and MPA plasma exposure (as reviewed in McDermott et al (31), and some HCT centers personalize MMF doses to a target MPA exposure. (32) We recently observed that low total MPA plasma exposure was associated with increased grades 3–4 acute GVHD and increased non-relapse mortality in nonmyeloabative HCT recipients with an unreIated donor graft.…”
Section: Discussionmentioning
confidence: 99%
“…In patients receiving a related donor graft after nonmyeloablative conditioning, however, total MPA plasma exposure was not associated with clinical outcomes and additional biomarkers, such as recipient pretransplant IMPDH activity, are of interest. (31) Unfortunately, because of a concurrent clinical trial comparing TBI vs. fludarabine/TBI in related donor graft recipients,(33) there is a paucity of nonmyeloablative HCT participants receiving an related donor graft in this reported population (Table 1). …”
Section: Discussionmentioning
confidence: 99%